Creation of functional film materials based on nanocrystals, quasicrystals, and approximant phases of the Ti-Zr-Ni system - Shpakov, Dmytro (National Technical University "Kharkiv Polytechnic Institute", 2025)
This work focuses on the development and investigation of new functional nanomaterials in the form of thin-film coatings based on nanocrystals, quasicrystals, and approximant phases (1/1, 2/1) in the Ti-Zr-Ni system. Special attention is given to the study of mechanical properties and potential applications of these coatings in hydrogen energy, aviation technology, and nuclear fusion energy.
Keywords: quasicrystals; nanomaterials; approximants; thin-film coatings; Ti-Zr-Ni; hydrogen energy; thermal resistance; mechanical properties